ANALISIS PENGGUNAAN KAPUR TOHOR (CaO) UNTUK MENINGKATKAN KUALITAS AIR LIMBAH TAMBANG DI CV. BK PROVINSI KALIMANTAN TENGAH - Purba, Aron; Indrajaya, Fahrul; Noveriady , Noveriady; Aulia, Syarifah (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2024)
Open-pit mining can lead to the degradation of environmental quality in the areas where mining activities occur, one of which is the presence of mining wastewater that can disrupt ecosystems. The purpose of this study is to understand the liming process on mining wastewater samples and to determine the effect of quicklime on the quality of mining wastewater. The methods used in this research include qualitative and descriptive approaches. The research location is at CV. BK in Lemo I Village, Teweh Tengah District, and Bintang Ninggi I and II Villages in Teweh Selatan District. The study was conducted in early 2023. The data for this research consists of primary data, including mining wastewater samples, the quality of mining water, and doses of quicklime; as well as secondary data, including environmental management maps, regional geological maps, and location maps.